Block chain based Secure Data Sharing in Cloud-Based IOT System - Umar M Mulani, Manoj Patil (Mathematical Statistician and Engineering Applications, 2022)
Numerous security and privacy issues with IoT systems must be properly considered. There are benefits and drawbacks to both centralized and decentralized methods. Delays, computing expenses, and energy concerns constrain decentralized systems, whereas scalability constrain centralized solutions. We proposed a multi-agent architecture to enable straightforward, decentralized IoT access control security solutions. The responsibility for providing the necessary security for cloud computing, local IoT device connectivity, fog node security, core fog node security, and access control falls on blockchain management. The proposed architecture is a versatile strategy that may be applied to various IoT applications. Additionally, because they tend to focus on access control issues in specific IoT applications, such as smart homes, earlier research has not effectively addressed IoT obstacles. The authors are aware that the application and effectiveness of the solution in comparison to similar studies must be assessed during the implementation and testing phases.